Asymptotic behavior and periodic nature of two difference equations
We discuss the global asymptotic stability of the solutions of the difference equations x_n+1 = x_n−2 ±1 + x_nx_n−1x_n−2 , n = 0,1,…, where the initial conditions x_−2, x_−1, x_0 are real numbers., number=6, journal=Ukrains’kyi Matematychnyi Zhurnal, author=Khalaf-Allah, R., year=2009, month=Jun., pages=834–838